Immunogenicity of two COVID-19 vaccines used in India: An observational cohort study in health care workers from a tertiary care hospital - Arankalle, Vidya; Kulkarni-Munje, Archana; Kulkarni, Ruta; Palkar, Sonali; Patil, Rahul; Oswal, Jitendra; Lalwani, Sanjay; Mishra, Akhilesh Chandra (Frontiers in Immunology, 2022)
COVID-19 pandemic witnessed rapid development and use of several vaccines. In India, a country-wide immunization was initiated in January 2021. COVISHIELD, the chimpanzee adenoviral-vectored vaccine with full-length SARS-COV-2 spike insert and COVAXIN, the whole virus-inactivated vaccines were used. To assess and compare immune response of health-care-workers to COVISHIELD (n=187) and COVAXIN (n=21), blood samples were collected pre-vaccination, 1month post-1/post-2 doses and 6months post-dose-2 and tested for IgG-anti-SARS-CoV-2 (ELISA) and neutralizing (Nab,PRNT50) antibodies. Spike-protein-specific T cells were quantitated by IFN-γ-ELISPOT. In pre-vaccination-antibody-negative COVISHIELD recipients (pre-negatives, n=120), %Nab seroconversion (median, IQR Nab titers) increased from 55.1% (16, 2.5-36.3) post-dose-1 to 95.6% (64.5, 4.5-154.2, p<0.001) post-dose-2 that were independent of age/gender/BMI. Nab response was higher among pre-positives with hybrid immunity at all-time points (p<0.01-0.0001) and independent of age/gender/BMI/Comorbidities. Post-dose-2-seroconversion (50%, p<0.001) and Nab titers (6.75, 2.5-24.8, p<0.001) in COVAXIN-recipients were lower than COVISHIELD. COVAXIN elicited a superior IFN-γ-T cell response as measured by ELISPOT (100%; 1226, 811-1532 spot forming units, SFU/million PBMCs v/s 57.8%; 21.7,1.6-169.2; p<0.001). At 6months, 28.3% (15/53) COVISHIELD and 3/3COVAXIN recipients were Nab-negative. T cell response remained unchanged. During immunization, COVID-19 cases were detected among COVISHIELD (n=4) and COVAXIN (n=2) recipients. At 6months, 9cases were recorded in COVISHIELD-recipients. This first-time, systematic, real-world assessment and long-term follow up revealed generation of higher neutralizing antibody titers by COVISHIELD and stronger T-cell response by COVAXIN. Diminished Nab titers at 6months emphasize early booster. Immunogenicity/efficacy of vaccines will change with the progression of the pandemic needing careful evaluations in the field-settings.